Ida B : [compact disc, unabridged] : --and her plans to maximize fun, avoid disaster, and (possibly) save the world - Hannigan, Katherine (Listening Library, 2004)
In Wisconsin, fourth-grader Ida B spends happy hours being home-schooled and playing in her family's apple orchard, until her mother begins treatment for breast cancer and her parents must sell part of the orchard and send her to public school.